2007
DOI: 10.1016/j.ijrobp.2006.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transforming Growth Factor-β Signaling in Normal Lung Epithelial Cells Confers Resistance to Ionizing Radiation

Abstract: Purpose-To address the functional role of radiation-induced TGF-β signaling in normal epithelial background, we selected spontaneously immortalized lung epithelial cell line derived from the normal lung tissue of dominant-negative mutant of TGF-β RII (ΔRII) transgenic mouse that expressed conditionally ΔRII under the control of metallothionein promoter (MT-1) and assessed it's impact on radio-sensitivity.Method and Materials-Spontaneously immortalized lung epithelial cell culture (SILECC) was established and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Luciferase activity was measured after 24 hours of TGF-β 1 treatment using the Dual-Luciferase Reporter Assay System (Promega) as described (32). The firefly luciferase activity was normalized to the activity of the internal control (Renilla luciferase, pRL vector) that was co-transfected along with the reporter vector.…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase activity was measured after 24 hours of TGF-β 1 treatment using the Dual-Luciferase Reporter Assay System (Promega) as described (32). The firefly luciferase activity was normalized to the activity of the internal control (Renilla luciferase, pRL vector) that was co-transfected along with the reporter vector.…”
Section: Methodsmentioning
confidence: 99%
“…The absence or low level of expression of RII or Smad4 is thought to be reason for resistance to chemo- or radiotherapy in lung cancer. We showed that restoration of RII receptor in normal lung cells that specifically harbored defective TGF-β signaling pathway increased sensitivity to radiation and will decrease malignant potential by increasing apoptosis (87). The wild-type p53 protein is reported to affect radiation responsiveness in several types of cancers, with radiation causing an accumulation of p53 protein that initiates apoptosis.…”
Section: Radiation-induced Tgf-beta Signalingmentioning
confidence: 99%
“…Based on previous studies on eight human colorectal cancers, it was postulated that radiation-induced sensitization to TGF-β require functional p53, but our study demonstrated that MIA PaCa-2/RII cells with restored TGF-β signaling are sensitive to radiation despite the fact that these cells harbor a mutated p53 gene (47). Importantly, radiation failed to induce p21 protein expression in parental MIA PaCa cells, since both the p53 and TGF-β pathways are not functional in these cells, but after restoration of functional RII, radiation exposure resulted in p21 protein elevation (87). …”
Section: Radiation-induced Tgf-beta Signalingmentioning
confidence: 99%
“…Many studies suggest inhibiting TGFβ1 could protect lungs, kidneys, blood vessels, liver, skin, etc. from radiotherapy-induced injury [3033]. In addition, TGF-β1 inhibitor can attenuate tumor cell migration [34] and enhance sensitivity to radiation therapy in pancreatic cancer, glioblastoma and breast cancer [3537].…”
Section: Discussionmentioning
confidence: 99%